Design and optimisation of single-layered on-metal tag antennas for ultra-high-frequency radio frequency identification - Muthukannan, Murugesh (2023)
In this thesis, four compact single-layered planar antennas are proposed for designing four novel flexible UHF RFID tags that can be used for different onmetal applications. The first two tag antennas can generate directional read patterns above the metal plate. When being placed on metal, the other two tag antennas can be read in all directions in the azimuth plane. The initial pair of antennas are compact UHF tag antennas designed for on-metal applications. Each antenna features a square ring that is loaded with two distributed inductors, which enable miniaturization of the antenna's size. The incorporation of these distributed inductors enhances the antenna's resistance, resulting in a strong conjugate impedance match with the microchip. As a result, these tag antennas can achieve a maximum read distance of 9 meters when placed on metal, using an EIRP power of 4W. The second antenna is a single-layer patch antenna with two complementarily placed C-shaped patches, designed for a metal-mountable tag with wide frequency tuning capabilities. The close coupling of the patches generates enough antenna reactance to tune the resonance frequency over a broad range from 920 MHz to 1.18 GHz without external lumped components. It achieves a maximum read distance of 9 meters on metal at 3.28W EIRP. The third antenna is a new serpentine patch ZOR antenna used for designing an anti-metal tag with omnidirectional radiation on metallic surfaces. It features two closely stacked serpentine patches that support the zeroth-order resonance. The tag's resonance frequency can be adjusted by modifying the serpentine patch parameters. The tag is simple to manufacture with no complex structures and achieves good omnidirectional radiation. At 915 MHz with an EIRP of 4W, it has a maximum reading distance of around 10 meters on metal and provides uniform spatial coverage (> 8 meters) across the azimuth plane. The fourth antenna is a polarization-insensitive planar patch antenna designed for metal-mountable tags. It uses closely overlapped patches to create a large capacitive reactance, reducing the resonance frequency. By employing reversedirection surface currents and orthogonal fields, the antenna becomes polarization-insensitive, and readable from almost all directions above the metal surface. It achieves a maximum read distance of 15 meters on metal with an EIRP power of 4W. These tag prototypes are simple in structure, and they can be etched out of a piece of single-sided copper-clad polyimide film. The shorting stubs and shorting walls can be tactfully wrapped around the edges, and they do not require additional PCB fabrication processes. In these designs, different methodologies are used to provide multiple degrees of tuning freedom, and each design has a ground plane to isolate the radiator from the backing object. The transmission line and equivalent circuit models have also been derived for analysing the impedance characteristics. The proposed tag antennas have a compact size, low profile, simple structure, slight flexibility, and they can achieve better read performances than the other contemporary ones.